2015
DOI: 10.1007/s10967-015-4666-4
|View full text |Cite
|
Sign up to set email alerts
|

Geographic determination of the growing origins of Jamaican and international coffee using instrumental neutron activation analysis and other methods

Abstract: This study was undertaken to determine whether elemental analysis could distinguish the growing origins of Jamaican versus international coffee and identify intra-island growing regions. Twenty-four samples of roasted and ground coffee and soluble coffee were collected and analysed using instrumental neutron activation analysis and inductively coupled plasma optical emission spectroscopy. Sixteen elements were selected for statistical evaluation. Soluble clustered discretely from roasted and ground samples. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Furthermore, harvest year and degree of ripeness were nonsignificant [35]. Another study employing ICP-optical emission spectrometry (OES) found that metal element content could discriminate the coffee origin from different countries in South America [36], the inter-Mexican region [37], cross-continental samples [38], Ethiopian coffee from 11 different regions [39] and different postharvest process [40], and Jamaican coffee against non-Jamaican [41]. In agreement with Valentin and Watling [35], Habte et al [39] confirmed that harvest year did not significantly influence coffee's elemental compounds.…”
Section: Analytical Approachesmentioning
confidence: 99%
“…Furthermore, harvest year and degree of ripeness were nonsignificant [35]. Another study employing ICP-optical emission spectrometry (OES) found that metal element content could discriminate the coffee origin from different countries in South America [36], the inter-Mexican region [37], cross-continental samples [38], Ethiopian coffee from 11 different regions [39] and different postharvest process [40], and Jamaican coffee against non-Jamaican [41]. In agreement with Valentin and Watling [35], Habte et al [39] confirmed that harvest year did not significantly influence coffee's elemental compounds.…”
Section: Analytical Approachesmentioning
confidence: 99%
“…However, their precise representation and quantity depend on many variables, such as the genotype of the coffee tree and its growing conditions (defined by the soil, climate, altitude, and other factors), post-harvest processing methods, the degree of the green coffee beans roasting, storage and distribution conditions, as well as coffee brewing methods [ 13 , 20 , 21 , 24 , 44 , 47 , 60 , 61 , 62 ]. Many studies have already been published in which elements [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], triglycerides [ 72 ], tocopherols [ 62 , 72 , 73 , 74 ], trigonellines [ 18 , 75 , 76 , 77 , 78 , 79 ], diterpenes [ 80 , 81 , 82 ], carbohydrates [ 76 , 83 , 84 , 85 , 86 , 87 ], polyphenols [ 36 , 37 , 39 , 65 , 75 , 76 , 77 , 78 , 88 , 89 , 90 , …”
Section: Introductionmentioning
confidence: 99%
“…Valentin and Watling [4] employed Inductively Coupled Plasma spectroscopies (ICP) to determine the provenance of coffee samples from 15 countries, based on the contents of 59 elements. Antoine et al [5], with measurements through Neutron Activation Analysis (NAA) and other methods, determined the origin of ground coffee consumed in Jamaica. Debastiani et al [6] analyzed Brazilian coffee samples with Particle Induced X-ray Emission (PIXE).…”
Section: Introductionmentioning
confidence: 99%